2020
DOI: 10.1111/all.14197
|View full text |Cite
|
Sign up to set email alerts
|

Comel‐Netherton syndrome: A local skin barrier defect in the absence of an underlying systemic immunodeficiency

Abstract: Background: Comel-Netherton syndrome (NS) is a rare autosomal disease, characterized by severe skin disease, hair shaft defects, atopic diathesis, and increased susceptibility for skin infections. Since patients with NS suffer from recurrent infections, it has been hypothesized that an underlying immunodeficiency attributes to this. Here, we studied clinical and immunological characteristics of the cohort of NS patients in the Netherlands in order to identify whether potential immunodeficiencies result in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…40 Therefore, the skin barrier defect is likely to trigger an immune response in NS patients with no evidence for an immunodeficiency, as previously suggested. 14 Of note, the inflammatory properties of IL-17 and IL-36 pathways are enhanced by their capacity to mutually regulate each other. [41][42][43] Studies have shown that IL-36 cytokines are the most upstream mediator of skin inflammation in murine models of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…40 Therefore, the skin barrier defect is likely to trigger an immune response in NS patients with no evidence for an immunodeficiency, as previously suggested. 14 Of note, the inflammatory properties of IL-17 and IL-36 pathways are enhanced by their capacity to mutually regulate each other. [41][42][43] Studies have shown that IL-36 cytokines are the most upstream mediator of skin inflammation in murine models of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…16,24 NS patients also displayed an enrichment in circulating lymphocytes expressing IL-17 and IL-22, 25 suggesting that NS could be a T H 17-driven disorder resulting from skin barrier impairment. 14 The involvement of the T H 17 axis in NS pathogenesis is supported by the successful treatment of NS patients with anti-IL-17A antibodies. [26][27][28] Although anti-IL-17A therapy results in a significant clinical benefit, we recently reported that improvement could not be durably sustained, suggesting that other biological pathways are likely to contribute to NS pathogenesis.…”
Section: Typical Ichthyosis Linearis Circumflexa (Ns-ilc) or Scaly Erythroderma (Ns-se)mentioning
confidence: 99%
See 1 more Smart Citation
“…In a majority of patients, the erythroderma present at birth gradually evolves into ichthyosis linearis circumflexa with typical ‘double-edged’ scales ( 30 ). Although symptoms can vary widely, most patients experience extensive pruritus and recurrent skin infections ( 24 , 29 , 31 ). Furthermore, NS is considered an immunodeficiency, based on previous studies that showed defects in immune cell function ( 29 , 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NS is considered an immunodeficiency, based on previous studies that showed defects in immune cell function ( 29 , 32 , 33 ). However, a recent study suggests a local skin barrier defect in the absence of an underlying systemic immunodeficiency ( 24 ).…”
Section: Introductionmentioning
confidence: 99%